Penulisan Cerita Pendek Mengenai Lingkungan Alam di Mubut Darat - Aji, Satriya Bayu; Antoni, Condra; Siahaan, Arta Uly (Politeknik Negeri Batam, 2023)
The shift from an industrial city to a tourist city in Batam may have a negative impact on the sustainability of its coastal environment, one of which is on Mubut Darat, which is planned to become a tourist destination. In addition to science, there is a need for a cultural approach through ecocriticism to reduce and prevent the negative impact of damage to the environment, disguised under the need for development. It is clear that humans are part of nature and the dualism of culture and nature is one of the main issues in ecocriticism. The main purpose of this article is to explore the perspective of the local community regarding the development of tourist villages and the problems of damage to the environment that goes along with it. The data were obtained through interviews with the managers of Mubut Darat beach and Batam Pos crews. Through the interview, informants are invited to participate in a dialogue, receive feedbacks, and express their opinions. The resulting short story is published in the form of a short story in Batam Pos' Zetizen column as a medium to promote Mubut Darat beach and offer readers perspective on environmental issues. According to the interview, the characters, plot, and setting of the story are interesting and easy to understand. However, the issue of environment is not suitable to be conveyed through the genre of romance.